2018
DOI: 10.5582/bst.2018.01048
|View full text |Cite
|
Sign up to set email alerts
|

Bi-specific ligand-controlled chimeric antigen receptor T-cell therapy for non-small cell lung cancer

Abstract: Our goal is to develop a switch-controlled approach to enable better control of reactivity and safety of chimeric antigen receptor (CAR)-T therapy for non-small-cell lung cancer (NSCLC). Lentiviral transduction was performed to generate anti-FITC CAR-T cells and target cells stably expressing either isoform of the folate receptor. Colorimetric-based cytotoxic assay, enzyme-linked immunosorbent assay, and multiparametric flow cytometry analysis were used to evaluate the specificity and activity of CAR-T cells i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…262,263 This established a pseudoimmunological synapse with FITC-CAR T cells and cells expressing either FRα or FRβ, which is also highly expressed on TAMs in the tumor microenvironment. 261 Potent antigen-specific and dose-dependent in vitro efficacy was demonstrated against NSCLC and macrophage cell lines. Further preclinical testing is required to determine the efficacy targeting both the tumor and tumor microenvironment in NSCLC.…”
Section: Ctla-4 Antibodymentioning
confidence: 99%
See 1 more Smart Citation
“…262,263 This established a pseudoimmunological synapse with FITC-CAR T cells and cells expressing either FRα or FRβ, which is also highly expressed on TAMs in the tumor microenvironment. 261 Potent antigen-specific and dose-dependent in vitro efficacy was demonstrated against NSCLC and macrophage cell lines. Further preclinical testing is required to determine the efficacy targeting both the tumor and tumor microenvironment in NSCLC.…”
Section: Ctla-4 Antibodymentioning
confidence: 99%
“…A switch-controlled approach was recently developed to enable better control of reactivity and safety of CAR-T therapy for NSCLC. 261 CAR-T cells targeting fluorescein isothiocyanate (FITC), were generated in conjunction with an intermediate antigen switch composed of folate bound to FITC, thereby binding the folate receptor α (FRα) chain, a cell surface protein that is expressed in over 70% of lung adenocarcinomas. 262,263 This established a pseudoimmunological synapse with FITC-CAR T cells and cells expressing either FRα or FRβ, which is also highly expressed on TAMs in the tumor microenvironment.…”
Section: Ctla-4 Antibodymentioning
confidence: 99%
“…Another semi-synthetic adaptor CAR system relies on scFv-based α-FITC CARs targeting the synthetic dye fluorescein isothiocyanate (FITC) that is chemically coupled to various tumor-specific adaptor molecules ( Figure 2c) [41]. The first proof of concept studies by Tamada and colleagues demonstrated that T cells carrying 3rd generation α-FITC CARs are able to elicit potent anti-tumor responses in the presence of FITC-labeled cetuximab, rituximab, and trastuzumab [41][42][43][44][45][46][47][48][49]. Over time, different classes of FITC-conjugated adaptor molecules were studied, including targeting compounds based on fragments of antigen binding (Fabs) [43,44] and small molecules [42,[45][46][47][48][49].…”
Section: Tag-binding Adaptor Carsmentioning
confidence: 99%
“…Another type of switch molecule is the FITC-folate system. Instead of using an antibody-recognizing TAA, folate, which recognizes the folate receptor alpha (FOLR1) receptor that is normally overexpressed on~40% of human cancer cells such as breast, lung, uterus, and ovarian [75][76][77], was linked to FITC, which could then be recognized by the anti-FITC antibody connected to CAR on the CAR-T cells [78][79][80]. Therefore, tumor cells overexpressing FRα is recognized by folate that is linked to FITC, and then FITC is recognized by the anti-FITC antibody, resulting in CAR-T cell activation.…”
Section: Universal Car-t By Switch Molecules For Allogenic Applicationmentioning
confidence: 99%